2014
DOI: 10.1016/j.atherosclerosis.2013.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Family history of coronary heart disease and the incidence and progression of coronary artery calcification: Multi-Ethnic Study of Atherosclerosis (MESA)

Abstract: Objective We evaluated family history as a predictor of incident and progressive coronary artery calcium (CAC) using data from the Multi-Ethnic Study of Atherosclerosis (MESA). Background MESA is a multi-center prospective study of 6,814 asymptomatic individuals. The relationship between family history of coronary heart disease (CHD) and CAC incidence or progression has not been described previously. Methods A total of 5,099 participants had detailed information about family history of CHD (late versus pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 47 publications
3
27
0
Order By: Relevance
“…Both active smoking and exposure to smoke are associated with the progression of atherosclerosis. The outcome of our observation are quite similar to that of George Howard et al (1998) 16 where, although most of the participants were females yet developed atherosclerosis as they were passively exposed to smoking. 36%(18) of subjects virtually belonged to upper lower class (IV), 24% (12) to upper middle class(II), 20%(10) from lower middle class (III), 16% (8) upper class I and 4% (two) from lower class(V).…”
Section: Results Anddiscussionsupporting
confidence: 80%
“…Both active smoking and exposure to smoke are associated with the progression of atherosclerosis. The outcome of our observation are quite similar to that of George Howard et al (1998) 16 where, although most of the participants were females yet developed atherosclerosis as they were passively exposed to smoking. 36%(18) of subjects virtually belonged to upper lower class (IV), 24% (12) to upper middle class(II), 20%(10) from lower middle class (III), 16% (8) upper class I and 4% (two) from lower class(V).…”
Section: Results Anddiscussionsupporting
confidence: 80%
“…Parikh et al 25 demonstrated that a FHx of CAD was associated with increased subclinical coronary disease as measured by coronary artery calcification in the Framingham Offspring Study, which has also been confirmed in the MultiEthnic Study of Atherosclerosis. 28 Otaki et al 29 prospectively evaluated a subset of young patients (n=6308, men aged <55 years and women aged <65 years) from the Coronary CT Angiography Evaluation For Clinical Outcomes: An International Multicenter Registry (CONFIRM) who underwent CCTA for suspected CAD. They found that compared with patients without a positive FHx, patients with a positive FHx had a higher prevalence of any CAD (40% versus 30%; .…”
Section: Discussionmentioning
confidence: 99%
“…Offspring of parents with hypertension more often showed signs of hyperinsulinemia [23], high-normal blood pressure, increased serum CRP and leptin plasma levels compared with offspring without such parental history [8,[24][25][26][27]. In addition, it was recently demonstrated that family histories of premature and late coronary heart disease are associated with a progression of coronary artery calcium in offspring [28]. In offspring of patients who experienced a heart attack, increased levels of total cholesterol, VLDL cholesterol and LDL cholesterol from the age of 18 years were demonstrated previously [29].…”
Section: Discussionmentioning
confidence: 97%